search
Log In
Welcome to GO Mechanical, where you can ask questions and receive answers from other members of the community.
0 votes

If the Laplace transform of a function $f(t)$ is given by $\frac{s+3}{\left ( s+1 \right )\left ( s+2 \right )}$, then $f(0)$ is

  1. $0$
  2. $\frac{1}{2}$
  3. $1$
  4. $\frac{3}{2}$
in Differential Equations 4.9k points
recategorized by

1 Answer

0 votes
Apply Intitial Value theorem

140 points 2
Answer:

Related questions

0 votes
0 answers
The Dirac-delta function $\left ( \delta \left ( t-t_{0} \right ) \right )$ for $\text{t}$, $t_{0} \in \mathbb{R}$ ... $\mathcal{L}\left ( \delta \left ( t-a \right ) \right )=F\left ( s \right )$ is $0$ $\infty$ $e^{sa}$ $e^{-sa}$
asked Feb 22 in Differential Equations gatecse 1.6k points
0 votes
0 answers
Consider the following differential equation $\left ( 1+y \right )\frac{dy}{dx}=y.$ The solution of the equation that satisfies condition $y(1)=1$ is $2ye^{y}=e^{x}+e$ $y^{2}e^{y}=e^{x}$ $ye^{y}=e^{x}$ $\left ( 1+y \right )e^{y}=2e^{x}$
asked Mar 1 in Differential Equations jothee 4.9k points
0 votes
0 answers
If $y(x)$ satisfies the differential equation $(\sin x) \dfrac{\mathrm{d}y }{\mathrm{d} x} + y \cos x = 1,$ subject to the condition $y(\pi/2) = \pi/2,$ then $y(\pi/6)$ is $0$ $\frac{\pi}{6}$ $\frac{\pi}{3}$ $\frac{\pi}{2}$
asked Feb 22 in Differential Equations gatecse 1.6k points
0 votes
0 answers
The ordinary differential equation $\dfrac{dy}{dt}=-\pi y$ subject to an initial condition $y\left ( 0 \right )=1$ is solved numerically using the following scheme: $\frac{y\left ( t_{n+1} \right )-y\left ( t_{n} \right )}{h}=-\pi y\left ( t_{n} \right )$ where $\text{h}$ is the ... $h$ in the interval ___________________. $0< h< \frac{2}{\pi }$ $0< h< 1$ $0< h< \frac{\pi }{2}$ for all $h> 0$
asked Feb 22 in Differential Equations gatecse 1.6k points
0 votes
0 answers
The solution of $\dfrac{d^2y}{dt^2}-y=1,$ which additionally satisfies $y \bigg \vert_{t=0} = \dfrac{dy}{dt} \bigg \vert_{t=0}=0$ in the Laplace $s$-domain is $\dfrac{1}{s(s+1)(s-1)} \\$ $\dfrac{1}{s(s+1)} \\$ $\dfrac{1}{s(s-1)} \\$ $\dfrac{1}{s-1} \\$
asked Sep 18, 2020 in Differential Equations jothee 4.9k points
...